PENGARUH MENTAL TRAINING TERHADAP HASIL PUKULAN JARAK DEKAT ATLET SILAMPARI WOODBALL ACADEMY - Syafutra, Wawan; Remora, Hengky (LPPM Universitas Muhammadiyah Muara Bungo, 2024)
This study aims to determine the effect of mental training on the close-range hitting of silampari athletes in the woodball academy. The sample tested in this study was 10 athletes using an experimental research type using a one group pretest posttest design. The design of this experimental research is: (1) Determining the population and sample (2) Providing an initial test, namely a 20-meter close-range punch test (3) Providing treatment in the form of mental exercises (4) Conducting a final test (5) Calculating the pretest and posttest (6) Determining Significant or not. After being given mental training, a score of sig. 0.003 < 0.05, then H0 is rejected and Ha is accepted. So it can be concluded that there is an average difference between the results of the initial and final strokes, which means that there is a significant influence of applying mental training on the results of close shots of silampari woodball academy athletes.